2002
DOI: 10.1074/jbc.m206057200
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 2 Induction of the Osteocalcin Gene Requires MAPK Activity and Phosphorylation of the Osteoblast Transcription Factor, Cbfa1/Runx2

Abstract: Fibroblast growth factor 2 (FGF-2) is an important regulator of bone formation and osteoblast activity. However, its mechanism of action on bone cells is largely unknown. A major route for FGF signaling is through the mitogen-activated protein kinase (MAPK) pathway. We showed recently that this pathway is important for activation and phosphorylation of Cbfa1/ Runx2, an osteoblast-related transcription factor (Xiao, G

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
301
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(327 citation statements)
references
References 49 publications
21
301
1
4
Order By: Relevance
“…As noted above the expression of Runx2 can be stimulated by factors such as BMPs or inhibited by PTHrP. Runx2 phosphorylation can also regulate its transcriptional activity [Xiao et al, 2002] and additional factors also interact with Runx2 to regulate its transcriptional activity [Vega et al, 2004]. It is tempting to speculate that Runx2 may serve as a convergent point of multiple pathways orchestrating the transcription of Ihh, however, we have yet to determine if any of the factors regulating Runx2 play a role in regulation of Ihh in the growth plate.…”
Section: Prospectsmentioning
confidence: 92%
“…As noted above the expression of Runx2 can be stimulated by factors such as BMPs or inhibited by PTHrP. Runx2 phosphorylation can also regulate its transcriptional activity [Xiao et al, 2002] and additional factors also interact with Runx2 to regulate its transcriptional activity [Vega et al, 2004]. It is tempting to speculate that Runx2 may serve as a convergent point of multiple pathways orchestrating the transcription of Ihh, however, we have yet to determine if any of the factors regulating Runx2 play a role in regulation of Ihh in the growth plate.…”
Section: Prospectsmentioning
confidence: 92%
“…[31] ERK can stimulate the osteoblast-related gene expression by extracellular matrix-integrin receptor interaction, BMP-2, growth factors, and mechanostressing. [31][32][33][34] Xiao et al [35] demonstrated that stimulation of MAPK enhances the expression of osteocalcin, whereas the ERK-specific inhibitor (PD98059) inhibits expression. Our data show that PD98059 significantly inhibits AOPP-induced calcium deposition and OPN expression, indicating that AOPP can promote osteoblast differentiation and calcification of HASMCs via the ERK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Runt-related transcription factor-2 transcriptional activity is regulated by multiple pathways, such as the MAPK, PI3K, and STAT pathways (Lee et al, 2002;Xiao et al, 2002;Fujita et al, 2004). Runt-related transcription factor-2 also regulates several downstream target genes, such as extracellular matrix proteins, growth factors and receptors, mitochondrial proteins, and transcription factors (Gaikwad et al, 2001).…”
mentioning
confidence: 99%